Casas e a Memória: estudo sobre as edificações residenciais do Centro Histórico de Manaus - Oliveira, Lauriane Teixeira de (2023)
This research proposes a critical and discursive analysis of heritage, memory, place, identity and culture and their interactions and articulations with three residential buildings located in the Historic Center of Manaus. The Historic Center of the city is the result of its historical process of formation, and that presents constructions, such as buildings, palaces, squares and monuments, with high architectural and urbanistic standards. In the Old Center it is possible to find residential buildings with the same characteristics of the period of their construction. Therefore, the analysis consists in understanding the dynamics of the historical, socioeconomic and cultural formation process, which is essential in the interpretation of these factors applied to the architectural and urban production of the city, and especially of these buildings. The discussions and notes of the conceptual and epistemological trajectory of the cultural heritage and its legal interactions in heritage management are included. As well as the conceptual discussion of Historic Center, and the characterization of the area where these houses are located. In addition, it sought to relate and critically discuss the eclectic model and the slope called Belle Époque that influenced and determined the urban and architectural improvements, implying the adoption of materials and construction techniques, as well as assimilation and cultural imposition of foreign values and customs. Relating these aspects in the production of these houses and their characteristics. And finally, the contribution of the narratives obtained through interviews with the owners of these houses, relating their memories and their experiences with the theoretical and conceptual approaches of memory and place. In addition to the interactions and contributions of the narratives of the interviewees and their families to the memory and identity of the city. The study also pointed out the management of heritage, its applicability and functionality, and the new perspectives for safeguarding the built heritage. It was sought, therefore, to highlight the relevance of these narratives in the memorial and identity contribution, in the historical and symbolic architecture of these buildings and their interdisciplinary interpretations in studies on heritage and culture.